Identifying vertical partnership among automotive component companies: Empirical evidence from automotive industry in Jabodetabek, Indonesia - Donny Oktavian Syah (Journal of Economic Structures, 2019)
The goal of this research is to examine the relation between technology transfer, technical exchange, government role, and supplier performance of automotive industry in Jabodetabek, Indonesia. There are 99 companies in this study, consisting of 6 assembler companies, 59 tier-1 companies, and 34 tier-2 companies. The research was conducted by visiting sites and filling questionnaires based on Likert scale to the person in charge at middle-up management level who understand or is responsible for measuring product quality (purposive sampling). The result of the questionnaires was processed and analysed by partial least square path modelling (PLS-PM), using Smart PLS 3.2.7 software. The result showed that there was a significant impact of government role to technology transfer (p value 0.000), technology transfer to supplier performance improvement (p value 0.056), and technical exchange to supplier performance improvement (p value 0.074). However, there was no significant impact of government role to supplier performance improvement (p value 0.179).
Keywords: D21; D24; L62; L24; 330; Technology transfer; Technical exchange; Government role; Supplier performance improvement; Automotive industries in Jabodetabek; Indonesia